Research Techniques Made Simple: Stratum Corneum Tape Stripping - Keurentjes, Anne J; Jakasa, Ivone; Kezic, Sanja (Journal of investigative dermatology, 2021)
Stratum corneum (SC)-derived biomarkers can provide relevant information on the skin's antimicrobial, physical, and immunological barriers. The SC is easily accessible, and collection by adhesive tapes (tape stripping [TS]) is robust and minimally invasive. Given its minimal invasiveness and simplicity, TS is particularly useful for studies in the pediatric population and when repetitive sampling over time is desirable, for example, in clinical trials. The palette of SC biomarkers is expanding in a wide variety of research areas, benefiting from advances in multiplex immunoassays and omics approaches, including proteomics, lipidomics, and transcriptomics. Although there is increasing interest in collecting SC samples, the lack of TS standardization hampers its broader implementation in research and clinical practice. In this article, we address the TS procedure as well as methodological challenges that should be considered in the development of an optimal sampling strategy.